2015
DOI: 10.1155/2015/939418
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy for the Evaluation of Anesthetic Depth

Abstract: The standard-of-care guidelines published by the American Society of Anesthesiologists (ASA) recommend monitoring of pulse oximetry, blood pressure, heart rate, and end tidal CO2 during the use of anesthesia and sedation. This information can help to identify adverse events that may occur during procedures. However, these parameters are not specific to the effects of anesthetics or sedatives, and therefore they offer little, to no, real time information regarding the effects of those agents and do not give the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
1
25
0
2
Order By: Relevance
“…Also, the CTHR index changed in both the induction and awakening processes. The relative HbO 2 fluctuation had a similar trend, 28 while the trend is opposite in the case of Hb. 28 Interestingly, the Hb indices have similar trends in induction phase with another study, 48 which used propofol induction.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Also, the CTHR index changed in both the induction and awakening processes. The relative HbO 2 fluctuation had a similar trend, 28 while the trend is opposite in the case of Hb. 28 Interestingly, the Hb indices have similar trends in induction phase with another study, 48 which used propofol induction.…”
Section: Resultsmentioning
confidence: 80%
“…53,54 Hemandez-Meza et al had used the NIRS to measure the prefrontal activity during the induction and recovery states of GA, as well as compare the Hb value with BIS in outpatient elective colonoscopy and coloproctology surgery. 21,28,33 The results showed that the fNIRS have potential in assessing the DoA. However, there are still many problems.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations